2023
DOI: 10.3389/fmicb.2023.1264172
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of SARS-CoV-2 seroprevalence in dogs and cats in the Community of Madrid, Spain

Lidia Sánchez-Morales,
José M. Sánchez-Vizcaíno,
Lucas Domínguez
et al.

Abstract: To date, susceptibility to SARS-CoV-2 infection in domestic animals including cats and dogs has been described. However, it is important to carry out passive surveillance of these animals to be aware of any changes in the outcomes of the disease in these species that may occur. In this study, we have performed a retrospective study in which we analyzed sera (n = 1,640) from random animals: dogs (n = 1,381) and cats (n = 259) belonging to both homes (n = 1,533) and animal protection centers (n = 107) in the Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The seroprevalence of SARS-CoV-2 in domestic cats during the first pandemic wave in Europe in April-August 2020 was 4.2% in Germany, 3.3% in the UK, 4.2% in Italy and 6.4% in Spain ( Schulz et al, 2021 ). In 2021–2022, the prevalence of antibodies in cats from Europe varied from 1.3% in Italy ( Bianco et al, 2023 ), 2.7% in the Netherlands ( Duijvestijn et al, 2023 ), 3.2% in the UK ( Tyson et al, 2023 ) to 4.6% in Spain ( Sánchez-Morales et al, 2023 ). In Portugal, Oliveira et al (2022) found a correlation between contact of cats with infected people and the occurrence of antibodies to the virus, as the seropositivity of cats from COVID-19-positive and -negative households was 5.0% and 0.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence of SARS-CoV-2 in domestic cats during the first pandemic wave in Europe in April-August 2020 was 4.2% in Germany, 3.3% in the UK, 4.2% in Italy and 6.4% in Spain ( Schulz et al, 2021 ). In 2021–2022, the prevalence of antibodies in cats from Europe varied from 1.3% in Italy ( Bianco et al, 2023 ), 2.7% in the Netherlands ( Duijvestijn et al, 2023 ), 3.2% in the UK ( Tyson et al, 2023 ) to 4.6% in Spain ( Sánchez-Morales et al, 2023 ). In Portugal, Oliveira et al (2022) found a correlation between contact of cats with infected people and the occurrence of antibodies to the virus, as the seropositivity of cats from COVID-19-positive and -negative households was 5.0% and 0.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%